Youngstock Management as “The Key for Everything”? Perceived Value of Calves and the Role of Calf Performance Monitoring and Advice on Dairy Farms - Palczynski, Laura J.; Bleach, Emma C. L.; Brennan, Marnie L.; Robinson, Philip A. (Frontiers in Animal Science, 2022)
Replacement heifers are key to the future milking herd and farm economic efficiency but are not always prioritized on dairy farms. Dairy enterprises are comprised of components which compete for limited resources; scarce information about calf performance and the associated losses and (potential) gains on farms can mean calves are prioritized less in management and investment decisions. The research reported in this paper explored the personal and contextual factors that influence calf management decisions on dairy farms. Forty in-depth, semi-structured interviews were conducted with dairy farmers (26 interviews) and farm advisors (14 interviews) who were recruited using purposive and ‘snowball’ sampling. Interviews were recorded, transcribed and thematically analyzed. Six major themes were constructed from the interview data relating to: the perceived importance of youngstock management, the role and influence of calf rearers, calf performance monitoring, farmer engagement with information and advice, the quality of communication and advice, and veterinary involvement in calf rearing. Results indicated that although the wider dairy industry has promoted the importance of youngstock, calves often have not been fully integrated into the whole dairy farm system, nor culturally accepted as an integral part of the productive herd. Calves tended to be marginalized on farms, largely due to limited resources, lack of data monitoring, and their unrecognizsed potential, as well as social norms and scarcity of support structures impacting upon farm investment and management decisions. Many calf rearers were disappointed by the repetition and impractical nature of information in print media. Most farmers did not routinely consult their veterinarian about their calves, rather following a reactive treatment model even when a preventive herd health strategy was applied to the adult herd. Advisory structures often require a driven individual with calf-centric interest to prevent calves from being overlooked. Furthermore, advisory efforts often failed to motivate farmers to act on advice. These findings indicate the need for greater focus on how to achieve rearing targets by provision of technical and support structures to foster action towards improved calf wellbeing, and for the status of calves to be raised in line with their vital importance for the future dairy herd.